Size and Layer Dependence of Hybrid Graphene/h-BN Models Upon Heating - Nguyen, Hang Thi Thuy (Communications in Physics, 2020)
Different models contained graphene layer are studied via molecular dynamics simulation. Models are heated up from 50K to 8000K via Tersoff and Lennard-Jones potentials to have an entire picture about the evolution of graphene layer in the models upon heating. Various thermodynamic quantities, structural characteristics, and the occurrence of liquidlike atoms are studied, such as, the total energy per atom, the heat capacity per atom, the radial distribution functions, and the appearance of liquid atoms upon heating. The phase transition exhibits the first order. The melting point of graphene layer depends on the number of layers in the models while it does not depend on the size in the range of this study. The melting process of hybrid graphene and hexagonal boron nitride (h-BN) satisfies the first step towards Devil's staircase type phase transition. The melting point of hybrid graphene/h-BN is close to the one of experiment of graphite.